1991
DOI: 10.1002/jemt.1060190203
|View full text |Cite
|
Sign up to set email alerts
|

Fine structural characteristics of testicular cord formation in the developing rabbit gonad

Abstract: This paper presents morphological (light- and electron-microscopical) evidence for the role of the mesonephros in contributing cells to the differentiating indifferent gonad and, after sexual differentiation, to the testis. A continuous process is revealed during which segregation of cells occurs from the developing and regressing mesonephros. Additionally, the complementary role of the coelomic epithelium in gonadal ridge and testis formation is demonstrated. The differentiation of testicular cords, their rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 55 publications
10
37
1
Order By: Relevance
“…The present results on chinchilla rabbits confirm the previous morphological and ultrastructural description made by Wartenberg et al [1991] in developing gonads of New Zealand rabbits. Chronological and topographical cell distribution at the urogenital ridge suggest a continuous transfer of cells from renal corpuscles to the forming seminiferous cords.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present results on chinchilla rabbits confirm the previous morphological and ultrastructural description made by Wartenberg et al [1991] in developing gonads of New Zealand rabbits. Chronological and topographical cell distribution at the urogenital ridge suggest a continuous transfer of cells from renal corpuscles to the forming seminiferous cords.…”
Section: Discussionsupporting
confidence: 81%
“…The rabbit genital ridge is first detected at approximately 13 dpc (CS = 16) as a thickening at the inner surface of the mesonephros [Wartenberg et al, 1991;present Species Stage 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 Human (1) Days 20 22 24 28 30 33 36 40 42 44 48 52 54 55 58 Rabbit (2) Pig (3) Sheep (4) Dog (5) Mouse ( O'Rally and Müller, 1987;Butler and Juurlink, 1987;Theiler, 1972;Edwards, 1968). (1) study].…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive morphological studies have, furthermore, indicated that mesonephric cell contribution to the developing gonad is independent of the sex. In developing gonads of numerous mammalian species, the presence of 'cell streams' connecting the mesonephros tubuli and the developing gonad is suggested to indicate mesonephric cell contribution to both the ovarian and the testicular somatic cell population [mouse: Byskov et al, 1977;Byskov, 1978a;Upadhyay et al, 1979Upadhyay et al, , 1981Kanai et al, 1989;Karl and Capel, 1995;rat: Stein and Anderson, 1979;pig: Byskov et al, 1986;sheep: Zamboni et al, 1979sheep: Zamboni et al, , 1981Tisdall et al, 1999;human: Wartenberg, 1982;Wartenberg et al, 1991]. The mesonephric part of such 'cell streams' has been proposed to be the predominant cell contributor due to a comparable high mitotic activity [Stein and Anderson, 1979].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of several species have suggested mesenchymal tissue, coelomic epithelium and/or the mesonephros as being the only or participating source of the gonadal somatic cells. These studies are based on experimental evidence [Byskov, 1974;Byskov et al, 1977] or morphological indications [Gondos, 1969;Merchant, 1975;Pelliniemi, 1976;Byskov, 1978a;Upadhyay et al, 1979Upadhyay et al, , 1981Zamboni et al, 1979;Wartenberg, 1982;Yoshinaga et al, 1988;Kanai et al, 1989;Francavilla et al, 1990;Smith and Mackay, 1991;Wartenberg et al, 1991;Karl and Capel, 1995;Magras et al, 1997;Tisdall et al, 1999]. A more direct way of examining somatic cell contribution from either the coelomic epithelium or the mesonephros has been attempted by tracing the migration of cells carrying a marker MerchantLarios et al, 1993;Martineau et al, 1997;Brennan et al, 1998;Karl and Capel, 1998;Merchant-Larios and Moreno-Mendoza, 1998;Tilmann and Capel, 1999;Albrecht et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…The study of early testis differentiation in the rabbit (Wartenberg et al, 1991) illustrated that cells migrate from both the mesonephros and the coelomic epithelium to the developing testis. The migration of mesonephric cells takes place in XV but not XX gonads from 11.5 to 16.5 dpc in mice and contributes to the interstitial cell population; the myoid, the endothelial, and sorne cells closely associated with endothelial cells, but not in the Sertoli cells or the germ cells (Martineau et al, 1997;Buehr et al, 1993).…”
Section: B Cell Migrationmentioning
confidence: 99%